Survival Benefit and Cost Savings From Compliance With a Simplified 3-Hour Sepsis Bundle in a Series of Prospective, Multisite, Observational Cohorts. Issue 3 (March 2017) - Leisman, Daniel E.; Doerfler, Martin E.; Ward, Mary Frances; Masick, Kevin D.; Wie, Benjamin J.; Gribben, Jeanie L.; Hamilton, Eric; Klein, Zachary; Bianculli, Andrea R.; Akerman, Meredith B.; D'Angelo, John K.; D'Amore, Jason A.
Abstract : Objectives: To determine mortality and costs associated with adherence to an aggressive, 3-hour sepsis bundle versus noncompliance with greater than or equal to one bundle element for severe sepsis and septic shock patients. Design: Prospective, multisite, observational study following three sequential, independent cohorts, from a single U.S. health system, through their hospitalization. Setting: Cohort 1: five tertiary and six community hospitals. Cohort 2: single tertiary, academic medical center. Cohort 3: five tertiary and four community hospitals. Patients: Consecutive sample of all severe sepsis and septic shock patients (defined: infection, ≥ 2 systemic inflammatory response syndrome, and hypoperfusive organ dysfunction) identified by a quality initiative. The exposure was full 3-hour bundle compliance. Bundle elements are as follows: 1) blood cultures before antibiotics; 2) parenteral antibiotics administered less than or equal to 180 minutes from greater than or equal to two systemic inflammatory response syndrome "and" lactate ordered, or less than or equal to 60 minutes from "time-zero, " whichever occurs earlier; 3) lactate result available less than or equal to 90 minutes postorder; and 4) 30 mL/kg IV crystalloid bolus initiated less than or equal to 30 minutes from "time-zero." Main outcomes were in-hospital mortality (all cohorts) and total direct costs (cohorts 2 and 3). Measurements and Main Results: Cohort 1: 5, 819 total patients; 1, 050 (18.0%) bundle compliant. Mortality: 604 (22.6%) versus 834 (26.5%); CI, 0.9–7.1%; adjusted odds ratio, 0.72; CI, 0.61–0.86; p value is less than 0.001. Cohort 2: 1, 697 total patients; 739 (43.5%) bundle compliant. Mortality: 99 (13.4%) versus 171 (17.8%), CI, 1.0–7.9%; adjusted odds ratio, 0.60; CI, 0.44–0.80; p value is equal to 0.001. Mean costs: $14, 845 versus $20, 056; CI, –$4, 798 to –5, 624; adjusted β, –$2, 851; CI, –$4, 880 to –822; p value is equal to 0.006. Cohort 3: 7, 239 total patients; 2, 115 (29.2%) bundle compliant. Mortality: 383 (18.1%) versus 1, 078 (21.0%); CI, 0.9–4.9%; adjusted odds ratio, 0.84; CI, 0.73–0.96; p value is equal to 0.013. Mean costs: $17, 885 versus $22, 108; CI, –$2, 783 to –5, 663; adjusted β, –$1, 423; CI, –$2, 574 to –272; p value is equal to 0.015. Conclusions: In three independent cohorts, 3-hour bundle compliance was associated with improved survival and cost savings. Abstract : Supplemental Digital Content is available in the text.